Successful outcome in a rare case of pregnancy with familial hypercholesterolemia and dilated cardiomyopathy. Issue 9 (15th July 2013) - Singh, Neeta; Goyal, Manu; Kumar, Sunesh; Roy, Kallol Kumar
Abstract Familial hypercholesterolemia is a rare disorder characterized by high cholesterol levels and early cardiovascular disease. Early detection and treatment with statins and other hypolipidemic agents are effective in heterozygous patients. Low‐density lipoprotein apheresis and liver transplantation are treatment options in homozygous familial hypercholesterolemia. We report a case of a 27‐year‐old pregnant woman with familial hypercholesterolemia who presented with breathlessness and swelling in the joints. She had been taking statins previously, which were stopped and she had been put on low‐lipid and low‐residue diet to reduce the risk of acute coronary event and sudden intrauterine death. She was found to have dilated cardiomyopathy with 25% ejection fraction. At 36 weeks of gestation, we carried out cesarean section in view of poor biophysical profile. Familial hypercholesterolemia is a very rare disorder with only a few cases reported in the published work during pregnancy. Statins are contraindicated during pregnancy and diet modification remains the mainstay of therapy.